Um framework para a geração semiautomática de solos de guitarra - Cunha, Nailson dos Santos (2016)
This work deals with the development of a framework based on computational and optimization methods for algorithmic composition, more precisely, for the generation of guitar solos. The proposed approach was considered semiautomatic because it makes use of small melodic fragments (licks), previously created from human models. The solos generated are from the musical style Blues and they are applied over a well-known harmonic model called 12-Bar Blues. A licks database was created in which small instances containing a subset of them were randomly derived so as to diversify the possible candidates to be in the solo that will be generated. Once the instance is created, one solves an optimization problem that consists of determining the optimal sequence of a subset of licks by using a integer linear programming model. A set of rules was implemented for creating a matrix that de nes the transition cost between the licks. The outputs generated were stored in the MusicXML format and they can be read by most applications that provide support for this type of le and are capable of displaying it using the tablatures format. The solos created were evaluated by a sample of 173 subjects, classi ed as beginners, intermediates and professional musicians. A web application was developed to streamline the evaluation process. The results obtained show that the solos whose licks were optimally sequenced were statistically much better evaluated than those randomly sequenced, which indicates that the proposed methodology was capable of producing, on average, solos with a favorable percentage of acceptance.